The Impact of Short-term Combination of Limb Training and Pursed-lip Breathing in Chronic Obstructive Pulmonary Disease - Tarigan, Amira Permatasari; Ananda, Fannie Rizki; Pandia, Pandiaman; Susilo, Trisno; Maryaningsih, Maryaningsih; Anggriani, Anggriani (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The aim of this study is to determine the impact of short-term combination of upper and lower limb training on lung functions, functional capacity, and quality of life in stable chronic obstructive pulmonary disease (COPD). METHODS: This quasi-experimental study held in 2017 and included 20 participants diagnosed with COPD (forced expiratory volume in 1 second/forced volume capacity [FEV1/FVC] ≤70%). Combination of limb training with pursed-lip breathing held twice a week for 8 weeks. Lung functions, functional capacity, dyspnea scale, and quality of life were measured before, 1 month, and 2 months after training. RESULTS: In this study, there was a significant improvement of FVC after 2 months after training (p-value: 0.04), but not in FEV1. There was a significant improvement of CAT (p-value: 0.00) and modified medical research council (p-value: 0.04) after 1 month of training. There was a significant improvement of 6-min walking test mean after 2 months of training (p-value: 0.00). CONCLUSIONS: Short-term combination of limb training and pursed-lip breathing impacted positively on FVC, functional capacity, dyspnea scale, and quality of life in patients with COPD, but not in FEV1.